EFFICIENCY OF USING OFSET PRINTING MACHINE TO SPEED UP MAGAZINE PRINT TIME - Seno Aji Wicaksono; Yessy Yerta Situngkir; Sudiyamto Sudiyamto (Kreator, 2020)
Efficiency is a measure of success that is assessed in terms of the size of the source / cost and the length of time production takes to achieve the results of the activities carried out. The purpose of this thesis is to determine the efficiency of using machines to speed up printing time and the factors that affect production time as well as obstacles or problems at PT. Macananjaya Cemerlang, which makes production time inefficient. The writing method used is the descriptive method seen based on the use of literature as outlined in the referenced literature (bibliography), the method of field observation is direct observation by searching for accurate data during Industrial Practices. Based on the description above, it can be concluded that there are several problems that make the production time late than what has been scheduled due to various factors, especially in the selection of machines to streamline production time. Keywords— Efficiency, Printing, Production